Rethinking Parenthood in Islamic Law: A Maqāṣid al-Sharī‘ah Perspective on the Ethics of Voluntary Childlessness - Ahsanul Fahmi; Sahal Taqiyuddin (SHAHIH: Journal of Islamicate Multidisciplinary, 2026)
The legal and ethical position of voluntary childlessness in Islamic law remains contested because classical fiqh generally treats procreation as one of the central purposes of marriage, while contemporary Muslim societies increasingly encounter reproductive decisions shaped by economic pressure, gender equality, ecological anxiety, and personal autonomy. This article examines whether the childfree choice can be normatively discussed within Islamic legal reasoning without reducing piety to biological reproduction. Using qualitative library research, this study applies normative legal analysis based on maqāṣid al-sharī‘ah and maṣlaḥah reasoning to classical Islamic legal sources, contemporary tafsir and hadith studies, and recent scholarship on childfree discourse. The study finds that hifẓ al-nasl should not be interpreted only as the quantitative preservation of lineage, but also as the qualitative protection of offspring through welfare, dignity, education, and responsible parenting. This reinterpretation does not make childfree a universal Islamic ideal, but it allows a more contextual distinction between ideological rejection of parenthood and reproductive restraint based on harm, incapacity, or serious welfare considerations. The article contributes to Islamic family law by reconstructing the relationship between parenthood, prosperity, and piety through a maqāṣid-based ethical framework.